Wnt-Responsive Cancer Stem Cells Are Located Close to Distorted Blood Vessels and Not in Hypoxic Regions in a p53-Null Mouse Model of Human Breast Cancer. (5th May 2014) - Vadakkan, Tegy J.; Landua, John D.; Bu, Wen; Wei, Wei; Li, Fuhai; Wong, Stephen T.C.; Dickinson, Mary E.; Rosen, Jeffrey M.; Lewis, Michael T.; Zhang, Mei
Abstract : High-resolution imaging techniques were used to analyze the relationship between a Wnt-responsive cancer stem cell (CSC)-enriched population and the tumor vasculature using p53-null mouse mammary tumors transduced with a Wnt signaling pathway reporter. The results demonstrate that the combined strategy of monitoring the fluorescently labeled CSCs and vasculature using high-resolution imaging techniques provides a unique opportunity to study the CSC microenvironment. Abstract: : Cancer stem cells (CSCs, or tumor-initiating cells) may be responsible for tumor formation in many types of cancer, including breast cancer. Using high-resolution imaging techniques, we analyzed the relationship between a Wnt-responsive, CSC-enriched population and the tumor vasculature using p53-null mouse mammary tumors transduced with a lentiviral Wnt signaling reporter. Consistent with their localization in the normal mammary gland, Wnt-responsive cells in tumors were enriched in the basal/myoepithelial population and generally located in close proximity to blood vessels. The Wnt-responsive CSCs did not colocalize with the hypoxia-inducible factor 1α-positive cells in these p53-null basal-like tumors. Average vessel diameter and vessel tortuosity were increased in p53-null mouse tumors, as well as in a human tumor xenograft as compared with the normal mammary gland. The combined strategy of monitoring the fluorescently labeled CSCs and vasculature using high-resolution imaging techniques provides a unique opportunity to study the CSC and its surrounding vasculature.